2017
DOI: 10.1007/s11130-017-0621-6
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Predictive Glycaemic Response and Antioxidative Properties of Black Ear Mushroom (Auricularia auricula) Extrudates

Abstract: Black ear mushroom (Auricularia auricula) is an important genus of cultivated mushroom, which contains health benefits. Incorporating black ear (BE) mushroom into brown rice by extrusion changed the physicochemical, and more importantly, the nutritional characteristics of the extrudates. With increased incorporation of BE mushroom in the extrudates in vitro starch digestion of the different extrudates revealed significantly reduced starch digestion, suggesting a lower glycaemic index. In addition, incorporatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 31 publications
4
13
0
Order By: Relevance
“…The extruded snacks containing 20% MP showed the highest TPC, followed by 15% MP, 10% MP, and 0% MP. These results are consistent with those of Vallée et al () who reported that the incorporation of black ear mushroom in brown rice extrudates increased TPC (96–111 mgGAE/100 g) compared to the extrudates without mushroom. When considering effects of FM, it was found that increasing FM decreased TPC at all levels of MP (Table ).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The extruded snacks containing 20% MP showed the highest TPC, followed by 15% MP, 10% MP, and 0% MP. These results are consistent with those of Vallée et al () who reported that the incorporation of black ear mushroom in brown rice extrudates increased TPC (96–111 mgGAE/100 g) compared to the extrudates without mushroom. When considering effects of FM, it was found that increasing FM decreased TPC at all levels of MP (Table ).…”
Section: Resultssupporting
confidence: 93%
“…Another explanation for the lower ER is that the water reduced slip within the barrel, resulting in decreased torque; often the poor product expansion was due to insufficient pressure developed during extrusion (Hegazy, El‐Bedawey, Rahma, & Gaafar, ). This agreed with Vallée et al (), Cuj‐Laines et al () who reported that addition of back ear mushroom and grasshopper powder decreased ER of extrudes.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…It was not only the basis of energy and structural substances, but also participated in cell metabolism and physiological regulation processes. Original polysaccharides of mushrooms possessed antioxidant, antitumor, immunomodulatory, and antiglycemic activities (Zhao et al, 2014;Crespoa et al, 2017;Vallée et al, 2017;Xue et al, 2015). The bioactivities of original polysaccharides could be improved by chemical modifications, such as sulfation, carboxymethylation, and acetylation (Lu, Mo, Guo, & Zhang, 2012;Xu et al, 2009;Yuan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%